Gender Differences in Willingness to Compete: The Role of Culture and Institutions. Issue 618 (2nd February 2018) - Booth, Alison; Fan, Elliott; Meng, Xin; Zhang, Dandan
Abstract: Our Beijing-based laboratory experiment investigated gender differences in competitive choices across different birth-cohorts experiencing – during their crucial developmental-age – different institutions and social norms. To control for general time trends, we use Taipei counterpart subjects with identical original Confucian traditions. Our findings confirm that exposure to different institutions/norms during crucial developmental-ages significantly changes individuals' behaviour. In particular, Beijing females growing up during the communist regime are more competitively inclined than their male counterparts; their female counterparts growing up during the market regime; and Taipei females. For Taipei, there are no statistically significant cohort or gender differences in willingness to compete.